2018
DOI: 10.1108/bfj-11-2017-0622
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ risk perception, information seeking, and intention to purchase genetically modified food

Abstract: Purpose The purpose of this paper is to explore consumers’ intention to purchase genetically modified (GM) food from the perspective of risk information. Design/methodology/approach A conceptual model was proposed in which intention to purchase GM food is stimulated by the combination and complex effects of knowledge, risk perception, information need, information seeking and attitude. A face-to-face questionnaire survey was conducted in Jinan, Shandong Province. A total of 757 valid samples (55.6 percent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 37 publications
5
42
0
Order By: Relevance
“…We used RISP as a reference to construct a conceptual framework of consumers' food safety risk information-seeking intention, and then assessed critical factors of consumers' food safety risk information-seeking intention based on the responses from 774 WeChat users. The main conclusions from this research are as follows: (1) Risk perception is an important variable in predicting people's information-seeking intention, consistent with previous studies [11,15,25]. On the one hand, risk perception has a direct significant positive effect on consumers' information-seeking intention of food safety risk and this effect was more pronounced among the young, male, highly educated, and high-income groups.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We used RISP as a reference to construct a conceptual framework of consumers' food safety risk information-seeking intention, and then assessed critical factors of consumers' food safety risk information-seeking intention based on the responses from 774 WeChat users. The main conclusions from this research are as follows: (1) Risk perception is an important variable in predicting people's information-seeking intention, consistent with previous studies [11,15,25]. On the one hand, risk perception has a direct significant positive effect on consumers' information-seeking intention of food safety risk and this effect was more pronounced among the young, male, highly educated, and high-income groups.…”
Section: Discussionsupporting
confidence: 87%
“…Risk perception is also perceived hazard characteristics, which is used to describe people's cognitive evaluations of potential risk [15]. High risk perception may increase the uncertainty of consumers, so that they will obtain more information to access the risk, thus stimulating the consumers to search for more information [25,26]. If consumers judge that food safety risk will threaten their personal health or their families' health, they may have a stronger willingness to search for more food safety information in order to cope with risks.…”
Section: Risk Perceptionmentioning
confidence: 99%
“…First, it adds to our theoretical understanding of the factors associated with the formation of attitude towards GMF in China. More importantly, it adds to the relatively few studies that have used theories to examine consumer perceptions of GMF in China (e.g., [13,14]). The study also highlights the usefulness of MSD theory when predicting attitude towards GMF.…”
Section: Discussionmentioning
confidence: 99%
“…First, most published studies are from Western countries (e.g., [7,11,12]). Second, few studies in China have used theories to examine factors associated with public perceptions of GMF (e.g., [13,14,15]). Finally, within these theory-based studies, none has incorporated media factors even though genetically modified organisms and food have been a widely covered news topic globally [4,16,17] and in China [15,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Prati et al [21] found that Italian consumers have a weak intention to consume GM foods. However, Zhu et al [22] showed that Chinese consumers are willing to consume GM foods and such willingness is affected by their knowledge of the product and risk perceptions.…”
Section: Introduction To Biosafety Aspects Of Recombinant Dnamentioning
confidence: 99%